SAT0157 NINTEDANIB DOSE ADJUSTMENTS AND ADVERSE EVENTS IN PATIENTS WITH PROGRESSIVE AUTOIMMUNE DISEASE-RELATED INTERSTITIAL LUNG DISEASES IN THE INBUILD TRIAL. (2nd June 2020) - Volkmann, E.; Castellví, I.; Johnson, S.; Matteson, E.; Distler, J.; Seibold, J.; Costabel, U.; James, A.; Coeck, C.; Quaresma, M.; Cottin, V.
Abstract : Background: In the INBUILD trial in patients with progressive fibrosing ILDs, the adverse event (AE) profile of nintedanib was characterised predominantly by gastrointestinal AEs. Dose adjustments were used to manage AEs. Objectives: Assess AEs and dose adjustments in patients with autoimmune disease-related ILDs in the INBUILD trial. Methods: Patients with progressive fibrosing ILDs other than idiopathic pulmonary fibrosis were randomised to nintedanib 150 mg bid or placebo. Dose reductions to 100 mg bid and treatment interruptions were permitted to manage AEs. AEs over 52 weeks of treatment (or 28 days after last trial drug intake for patients who discontinued drug before week 52) were assessed in patients who received ≥1 dose of trial drug. Results: Of 663 patients in the INBUILD trial, 170 (82 nintedanib, 88 placebo) had autoimmune disease-related ILDs (89 RA-ILD, 39 SSc-ILD, 19 MCTD-ILD, 23 other autoimmune ILDs). In the nintedanib and placebo groups of patients with autoimmune disease-related ILDs, respectively, over 52 weeks, the proportions of patients with ≥1 dose reduction were 28.0% and 3.4%, with ≥1 treatment interruption were 31.7% and 10.2%, and with ≥1 dose reduction and/or treatment interruption were 40.2% and 12.5% (Table). Dose intensity (amount of drug administered divided by amount that would have been received had 150 mg bid been administered over 52 weeks or until permanent treatment discontinuation) was >90% in 80.5% of patients in the nintedanib group and 95.5% in the placebo group. AEs led to permanent treatment discontinuation in 17.1% and 10.2% of patients treated with nintedanib and placebo, respectively. Diarrhoea was the most common AE, reported in 63.4% and 27.3% of patients in the nintedanib and placebo groups, respectively. Diarrhoea AEs led to dose reduction, treatment interruption and permanent treatment discontinuation in 7.3%, 9.8% and 4.9% of patients in the nintedanib group, compared with 0%, 1.1% and 1.1% of patients in the placebo group, respectively. Of the nintedanib-treated patients who experienced ≥1 diarrhoea AE, 80.8% experienced 1 or 2 events and 76.9% experienced events that were mild at worst (Common Terminology Criteria for Adverse Events [CTCAE] grade 1). Conclusion: In the INBUILD trial, management of AEs via dose adjustments enabled most patients with autoimmune disease-related ILDs to remain on treatment for 52 weeks. Diarrhoea was the AE that most commonly led to dose adjustment. Disclosure of Interests: Elizabeth Volkmann Grant/research support from: Forbius, Corbus Pharmaceuticals, Consultant of: Boehringer Ingelheim, Forbius, Speakers bureau: Boehringer Ingelheim, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Sindhu Johnson Grant/research support from: Boehringer Ingelheim, Corbus Pharmaceuticals, GlaxoSmithKline, Roche, Merck, Bayer, Consultant of: Boehringer Ingelheim, Ikaria, Eric Matteson Grant/research support from: Pfizer, Consultant of: Boehringer Ingelheim, Gilead, TympoBio, Arena Pharmaceuticals, Speakers bureau: Simply Speaking, Jörg Distler Grant/research support from: Boehringer Ingelheim, Consultant of: Boehringer Ingelheim, Paid instructor for: Boehringer Ingelheim, Speakers bureau: Boehringer Ingelheim, James Seibold Shareholder of: BriaCell, Pacific Therapeutics, Consultant of: Atlantic, Blade Therapeutics, Eicos Sciences, Eiger Biopharmaceuticals, Indalo Therapeutics, Mitsubishi Tanabe Pharma, Bayer, Xenikos, Boehringer Ingelheim, Camurus, Corbus Pharmaceuticals, EMD Serono, Speakers bureau: Boehringer Ingelheim, Ulrich Costabel Consultant of: Boehringer Ingelheim, Roche, Fibrogen, Global Blood Therapeutics, Speakers bureau: Boehringer Ingelheim, Roche, AstraZeneca, Alexandra James Employee of: Employee of Boehringer Ingelheim, Carl Coeck Employee of: Employee of Boehringer Ingelheim, Manuel Quaresma Employee of: Employee of Boehringer Ingelheim, Vincent Cottin Grant/research support from: Boehringer Ingelheim, Roche, Consultant of: Boehringer Ingelheim, Roche, Actelion, Bayer, Gilead Sciences, Novartis, Promedior, Celgene, Galapagos, Galecto. He was a member of the INBUILD trial Steering Committee., Speakers bureau: Actelion, Boehringer Ingelheim, Novartis, Roche, Sanofi